Asymmetry during Functional Movement Screening and injury risk in junior football players: A replication study - Chalmers, S.; Debenedictis, T. A.; Zacharia, A; Townsley, S.; Gleeson, C.; Lynagh, M.; Townsley, A.; Fuller, J. T. (Scandinavian Journal of Medicine & Science in Sports, 2018)
An indicator of movement quality and potential injury risk during Functional Movement Screen (FMS) testing is the presence of asymmetry when comparing the left and right sides of the body. The aim of the study was to investigate the reproducibility of the injury risk model proposed in our previous research (Chalmers et al. 2017; derivation study) that showed an increased injury risk for elite junior Australian football players demonstrating =2 asymmetrical FMS sub-tests. We used a direct replication design. Players underwent pre-season FMS testing and an injury surveillance system monitored 277 male participants during the subsequent regular season competition. Designated club officials monitored the weekly competition participation of players. The definition of an injury was `a trauma or medical condition which caused a player to miss a competitive game`. Cox proportional hazards regression models were used to investigate the relationship between asymmetry and number of games played before first injury (i.e. survival time). The level of reproducibility was determined according to statistical significance, effect size, and subjective assessment. Demonstrating asymmetry during FMS testing was not associated with a significant increase in prospective injury risk in the replication study (p>0.05). Moreover, effect sizes (hazard ratios) from the derivation dataset were not within the 95% confidence intervals of the respective asymmetry predictor in the replication dataset. Subjectively, researchers were in agreement that the findings from the derivation data were not successfully reproduced. Clinicians and researchers should be cautious about using FMS asymmetry findings to derive injury risk for junior football players.